Anti-myeloma effect of pharmacological inhibition of Notch/gamma-secretase with RO4929097 is mediated by modulation of tumor microenvironment. Issue 5 (3rd May 2016) - Pisklakova, Alexandra; Grigson, Eileen; Ozerova, Maria; Chen, Feng; Sullivan, Daniel M.; Nefedova, Yulia
ABSTRACT: Multiple myeloma (MM), a blood cancer characterized by the uncontrolled proliferation of plasma cells, remains incurable by current therapy. Notch signaling has been implicated in the growth and chemoresistance of various cancer types including MM, and therefore we hypothesized that targeting the Notch pathway could be beneficial for the treatment of this disease. Here, we report an anti-tumor effect of Notch/γ-secretase inhibitor RO4929097 in a pre-clinical model of MM. We demonstrate that this effect was associated with decreased angiogenesis and significant down-regulation of TGF-β1. In addition, we also show that treatment with RO4929097 results in decreased number and functional activity of osteoclasts. Taken together, our data indicate that targeting Notch may be considered as a new strategy to be tested for MM therapy.